A REVIEW STUDY ON MOBILE PHONES VS BASIC AMENITIES IN THE INDIAN URBAN SLUMS DWELLERS - kumar.ch, Dr. Subha; Marapatla, Dr. Gangayya (IJRDO - Journal of Applied Management Science, 2017)
Needless to say, cell phones are part of our everyday life. But, the more overpowering question, as with every invention in our civilized world, is if there is a downside to our progress, and more specifically what levels of health problems has our use of the cell phone brought to our doorstep? On the surface of harmful cell phone use, is its potential to permanently damage brain cells through cellular phone frequencies. Believe it or not, science does not have a clear consensus on this issue. Instead of sounding a warning bell of despair, let’s look at both sides of the argument to uncover the issues surrounding this topic. In this research paper we studied about Basic amenities Vs Cell phones in India half of India’s homes have cell phones, but not toilets Census sheds new light on changing nation . These and many other contrasting facts of life have come out in Census 2011. The data on housing, household’s amenities and assets cast new light on country in the throes of complex transition where millions have access to state-of art technologies and consumer goods – but a larger number of lacks access to the most rudimentary facilities in the urban slums the Andhra Pradesh urban slums.